Peter Norton's essential concepts - Norton, Peter (Glencoe/McGraw-Hill, 2003)
Peter Norton's Essential Concepts 5th Edition is a state-of-the-art textthat provides comprehensive coverage of computer concepts. It is geared toward students learning about computer systems for the first time. Some of the topics covered are: an Overview of computers, input methods and out put devices, processing data, storage devices, operating systems, software, networking, Internet resources, and graphics.